Sveti Juraj - Lisac Underwater Site and Salt Production at the end of the Bronze Age (Archaeologia Adriatica, 2022)
The seaward view from above Sveti Juraj, which is located on the Velebit coast, about seven kilometres south of Senj, is dominated by the small island of Lisac. The proximity of the mainland and relatively shallow depth of the strait have attracted the attention of researchers and led to assumptions about the island’s connection to the mainland in the past. The paper presents the results of an underwater survey, which confirm the existence of archaeological potential under the surface of the strait. The site includes traces of maritime structures in the form of a communication embankment and an artificially created plateau. An analysis of ceramic artefacts suggests that significant spatial activities in the Lisac maritime landscape probably occurred during the Late Bronze Age. In processing the collected artefacts, the greatest attention was paid to briquetage finds.The term refers to a repertoire of products made of fired earth — supporting pillars and vessels — used in prehistoric salt production through forced seawater evaporation. The large quantity of fragments of these items strongly suggests a production site. In this context, the character of the site, the correlation between spatial characteristics of the location, as well as the requirements, needs and technological aspects of salt production through briquetage are discussed, with reference to the possible implications of this activity on contemporary social and economic frameworks at the microregional level.